HPA Frequencies in the Syrian Population - Hauck-Dlimi, Barbara; Damrah, Nouraldin; Achenbach, Susanne; Zimmermann, Robert; Zingsem, Jürgen; Ott, Stephan; Strobel, Joachim (Clinical Laboratory, 2019)
Background: Exposure to allogenic Human Platelet Antigens (HPAs) can lead to antibody formation causing different immunological reactions. Frequencies of common HPA antigens differ between ethnic groups and should be known to calculate potential alloimmunization risk. Syrian refugees are the largest group of applicants for asylum in Germany in 2017. However, no study on HPA antigen frequencies in the Syrian population exists.
CRIS-Team WoS Importer:2019-03-22